+0  
 
0
358
2
avatar

"In a function f where f(x)=kx+m the following applies;

f(x+4)-f(x)=2

f(m)=6

Decide the function f "

 

 

How do I solve this? Preferably step by step.

 Oct 22, 2017
 #1
avatar+98125 
+2

 f(x)=kx+m

f(x+4)-f(x)=2

f(m)=6

 

f(x+ 4) - f(x) = [ k (x + 4) + m] -  [kx + m]  =  2

So

 

kx + 4k + m  - kx - m  = 2

4k =  2

k = 1/2

 

And   f(m)  = 6

So

 

f(m)  =  (1/2) (m) + m  = 6

(3/2)m  = 6

m  = 4

 

So....the function is

 

f(x)  =  (1/2)x + 4

 

 

cool cool cool

 Oct 22, 2017
 #2
avatar
+1

Thanks! I really don't understand functions crying

Guest Oct 22, 2017

5 Online Users

avatar